Development of High Performance Anodes for Metal-Supported Fuel Cells. (2nd June 2015) - Rojek, Veronika; Roehrens, Daniel; Brandner, Marco; Menzler, Norbert H.; Guillon, Olivier; Opitz, Alexander Karl; Bram, Martin
Abstract : Metal-supported solid oxide fuel cells (MSCs) offer various potentials like cost reduction and abuse tolerance, which make them attractive for mobile applications such as auxiliary power units (APUs). The implementation of the metallic substrate requires specific adaption of SOFC processing technologies since sintering of functional layers at high temperatures under oxidizing atmosphere is restricted by the substrate. Therefore, one of the current challenges is the development of an anode layer, which can be sintered under reducing atmospheres, which improves i.a. the performance, the ageing behavior and the ability of the anode to withstand sulfur contaminations of the fuel gas. In the present work, a new anode concept is presented, which is based on a Ni/GDC cermet replacing the established Ni/YSZ cermet. The sintering study is supported by some preliminary results of characterizing the electrochemical performance of the Ni/GDC anodes by impedance spectroscopy. In addition, a thin GDC layer is currently used as diffusion barrier layer between the anode and the metallic substrate. A systematic study of the stability of this barrier layer under anode sintering conditions is given.